Synthesis and Biological Activities of Some Substituted 6H-Dibenzo [B,D] Pyran-6-One and 6,6-Dimethyl 6H-Dibenzo [B,D] Pyran Derivatives (Global Journal of Science Frontier Research, 2014)
Abstract not found